2018
DOI: 10.1080/2162402x.2018.1542918
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of immune checkpoints in the peripheral blood of breast and colorectal cancer patients

Abstract: Aberrant expression of immune checkpoints (ICs) in cancer creates an immunosuppressive microenvironment, which supports immune evasion of tumor cells. We have recently reported that epigenetic modifications are critical for ICs expression in the tumor microenvironment (TME) of primary breast cancer (PBC) and colorectal cancer (CRC). Herein, we investigated transcriptomic expression of ICs (PD-1, CTLA-4, LAG-3, TIM-3, TIGIT) and PD-L1 in peripheral blood of PBC and CRC patients, compared to healthy donors (HD).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 29 publications
(55 reference statements)
1
49
0
Order By: Relevance
“…Besides HLA-G and ILT-2, additional IC molecules such as programmed cell death protein-1 (PD-1), cytotoxic T-lymphocyte-associated protein (CTLA-4), T-cell immunoglobulin and mucin-domain containing-3 (TIM-3), and CD95 are associated in tumor-driven immune escape mechanisms acting locally at the tumor site or systemically in the peripheral blood (24)(25)(26). The continuous upregulation and co-expression of multiple IC, being often observed in cancer and chronic infections, are indicative for an immunosuppressive/exhausted phenotype of T cells and are associated with loss of effector functions and immunosurveillance (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Besides HLA-G and ILT-2, additional IC molecules such as programmed cell death protein-1 (PD-1), cytotoxic T-lymphocyte-associated protein (CTLA-4), T-cell immunoglobulin and mucin-domain containing-3 (TIM-3), and CD95 are associated in tumor-driven immune escape mechanisms acting locally at the tumor site or systemically in the peripheral blood (24)(25)(26). The continuous upregulation and co-expression of multiple IC, being often observed in cancer and chronic infections, are indicative for an immunosuppressive/exhausted phenotype of T cells and are associated with loss of effector functions and immunosurveillance (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Instead PD-L1 was more frequently detected in TN invasive tumors [75], signifying that the pattern of expression of these immune checkpoint molecules might vary in different phases of the disease (from in situ to invasive). In another study, peripheral blood from BC and colorectal cancer patients, observed LAG3 downregulation in patients with TIM3, TIGIT and PD-L1 upregulation [76], confirming the heterogeneous expression of these molecules also in circulating immune cells, and contributing to the complexity of this scenario.…”
Section: Lag3 In Human Breast Cancermentioning
confidence: 77%
“…Finally, the heterogenous expression between primary tumor and metastatic tissue also limits the use of IHC [47,48]. Blood-based assessment of PD-L1 is conceivable by protein, transcript, mutation, or methyla- In PBMCs Evaluation of PMBCs from BC patients demonstrated that PD-L1 promotor hypomethylation might be the reason for increased PD-L1 expression in PBMCs compared to matched tumor tissue [37]. Furthermore, the PD-1 promotor was shown to be hypermethylated in PBMCs compared to tumor tissue [37].…”
Section: Human Leukocyte Antigensmentioning
confidence: 99%
“…Blood-based assessment of PD-L1 is conceivable by protein, transcript, mutation, or methyla- In PBMCs Evaluation of PMBCs from BC patients demonstrated that PD-L1 promotor hypomethylation might be the reason for increased PD-L1 expression in PBMCs compared to matched tumor tissue [37]. Furthermore, the PD-1 promotor was shown to be hypermethylated in PBMCs compared to tumor tissue [37]. Methylation profiling via cfDNA might consequently be considered as molecular correlate for PD-L1 expression.…”
Section: Human Leukocyte Antigensmentioning
confidence: 99%